Recovery of Phenolic Compounds from Orange Peel Waste by Conventional and Assisted Extraction Techniques Using Sustainable Solvents - Blanca Sáenz de Miera; Raquel Cañadas; María González-Miquel; Emilio J. González (Frontiers in Bioscience-Elite, 2023)
Background: The valorization of orange peel waste (OPW) through the extraction of bioactive compounds is a clear example of the circular economy. OPW contains many value-added compounds, among which bioactive phenolic compounds (flavonoids and phenolic acids) could be extracted and used for industrial applications, such as pharmaceuticals or cosmetics. Methods: In this work, the extraction of phenolic compounds from orange peel was carried out by conventional (orbital shaker) and assisted (ultrasound and microwave) extraction techniques using deionized water, 80% (v/v) ethanol in water, and ethyl acetate as solvents. The effect of temperature, extraction time, and type of technique was evaluated and discussed following spectrophotometric (total phenolic content and total flavonoid content) and high-performance liquid chromatography (HPLC) analyses of the extracts. Results: The most effective extraction in terms of efficiency was achieved by microwave-assisted extraction using 80% (v/v) ethanol in water as the extraction solvent, at 373 K for 6 min, which obtained 7.2 ± 0.1 mg gallic acid equivalent (GAE)/g OPW and 13.3 ± 0.1 mg quercetin equivalent (QE)/g OPW, with the main bioactive compound extracted being hesperidin (58.2 ± 0.2 mg/g OPW). The most effective extraction in terms of energy consumption was achieved using ultrasound-probe-assisted extraction, yielding 8.8 ± 0.0 mg GAE/g OPW; 17.1 ± 0.1 mg QE/g OPW; 40.0 ± 0.2 mg hesperidin/g OPW, with an energy consumption of 18 kJ. Conclusions: Ultrasound and microwave-assisted extractions can be considered efficient extraction technologies for the valorization of OPW as they reduce extraction time and energy consumption and increase extraction yield.